Síntese e caracterização de oxinitretos lamelares com fórmula K1+xM2Nb3O10-xNx (M= Ca e Sr) aplicados na descoloração fotocatalítica do corante remazol amarelo ouro - Medeiros, Rayssa Barbosa de (2018)
Azo dyes are commonly used in the paper and textile industries, this class is characterized by having the chromophore (-N = N-) group attached to aromatic rings. It is known that these can be carcinogenic and/or mutagenic, on the basis of which their respective treatments are necessary. With this, heterogeneous photocatalysis appears as a growing medium in the literature, this may promote partial or total mineralization. Among the ceramic materials used in these processes, layered niobates of the perovskite type (KCa2Nb3O10 and KSr2Nb3O10), focus of this work, are composed of negatively charged lamellae, formed by the arrangement of stacked and distorted NbO6 octahedra with earth alkali metals (Ca2+ and Sr2+) present between the octahedra and monovalent cations in the interlamellar region. The objective of this work is to synthesize and characterize the mixed oxides KCa2Nb3O10 (KCNO) and KSr2Nb3O10 (KSNO) as well as their respective oxinitrets K1+xCa2Nb3O10-xNx (KCNO_N) and K1+xSr2Nb3O10-xNx (KSNO_N) applied in the photocatalytic discoloration of the Remazol Yellow dye Gold (RNL). In this work the KCNO and KSNO were obtained by the reaction in the solid state and by the method of the molten salt, already the KCNO_N and KSNO_N were obtained through ammonolysis. The X-ray diffraction (XRD), ultraviolet and visible (UV-Vis) absorption spectroscopy, infrared (IR) spectroscopy, Raman spectroscopy, area analysis (ED), X-ray fluorescence (EDX) and nitrogen elemental analysis, photoluminescence (PL) and thermogravimetric (TG / DTA) analysis. The materials presented a high organization when analyzed in the long range. The IR and Raman spectra confirmed the modifications made in the perovskite network, however, in the nitrided materials the possible existence of nitrogenous species inserted in an interstitial and substitutional way was observed. The results of elemental analysis showed the interconversion of the Dion Jacobson phase (DJ) to the Ruddlesden Popper (RP). PL spectra showed that the protonation and nitriding process promoted increased defects. BET analyzes did not show significant variations in surface areas. MET images showed the presence of nanofolia after exfoliation. In the DJ phase KCNO presented the best result, with 32% discoloration at pH 6, whereas in the RP phase the KSNO_N showed the highest discoloration, with 20%. These results can be directly related to the intensities of PL, which results in a greater or lesser recombination, and with this we can notice the differentiation of the activities of the obtained materials.